Legal Standards on Criticism of Government and Public Officials - bagher ansari (Faṣlnāmah-i Pizhūhish-i Huqūq-i ̒Umūmī, 2015)
Freedom of expression in regard to criticism directed toward government orpublic officials is faced with some challenges. On one hand, it reveals potentialor actual deficiencies and failures in their actions, decisions or institutions.Hence, it would be very constructive and beneficial to the public interest. On theother hand, through criticism, there might be potential false or unprovedattributions which can be considered as defamatory, subversive or revolutionarystatements. This essay tries to elaborate the legal standards based oninternational experiences and Islamic law, which seems to be proper for makingbalance between political speeches and protection of reputation of publicofficials or public trust to government. For this purpose, in the first chapter,theoretical basis for extensive protection of political speeches and in the secondpart, balance-standards are identified and studied.